Removal of organochlorine pesticides from water using virgin and regenerated granular activated carbon - MIRJANA B. NINKOVIĆ; RADA D. PETROVIĆ; MILA D. LAUŠEVIĆ (Journal of the Serbian Chemical Society, 2010)
Public water systems use granular activated carbon in order to eliminate pesticides. After saturation, the used activated carbon is regenerated and reused in order to reduce the costs of water production and minimize waste. In this study, the adsorption of 10 different chlorinated pesticides from water using columns packed with commercial virgin and regenerated granular activated carbon was simulated in order to compare their adsorption capacities for different chlorinated pesticides. The breakthrough curves showed that chlorinated pesticides from the group of hexachlorocyclohexane (HCH) were poorly adsorbed, followed by cyclodiens as averagely adsorbed and the derivatives of halogenated aromatic hydrocarbons (DDT) as strongly adsorbed. However, the adsorption capacity of regenerated granular activated carbon was considerably lower for tested pesticides compared to the virgin granular carbon. In addition, rinsing of the pesticides after the saturation point is a far more efficient process on regenerated carbon.